Defensive microbial symbionts in Hymenoptera. (13th April 2013) - Kaltenpoth, Martin; Engl, Tobias; Clay, Keith
Summary In all stages of their life cycle, insects are threatened by a multitude of predators, parasites, parasitoids and pathogens. The lifestyles and feeding ecologies of some hymenopteran taxa render them especially vulnerable to pathogen infestation. Specifically, development in sub‐terranean brood cells, mass provisioning of resources for the offspring and the life of social insects in large communities can enhance the risk of pathogen infestation and/or the spread of disease among conspecifics. To counteract these threats, insects have evolved mechanical, chemical and behavioural defences as well as a complex immune system. In addition to the host's own defences, some Hymenoptera are associated with protective symbionts. Leaf‐cutting ants, solitary digger wasps, bees and bumblebees engage in symbiotic interactions with bacteria that protect the adult host, the developing offspring or the food resources against microbial infections. In the well‐studied cases of ants and wasps, the protective activity is mediated by the production of antimicrobial secondary metabolites. In other symbiotic interactions, however, competitive exclusion and immune priming may also play an important role in enhancing protection. Phylogenetic studies indicate that the defensive associations in Hymenoptera are generally more dynamic than the intimate nutritional mutualisms, with horizontal transfer or de novo uptake of the symbionts from the environment occurring frequently. Mutualistic micro‐organisms can also significantly influence the outcome of host‐parasitoid interactions. Some insects are protected by symbiont‐produced toxins against parasitic wasps. Ichneumonid and braconid parasitoids, on the other hand, are associated with symbiotic viruses that are injected into the caterpillar host during oviposition and suppress its immune system to the advantage of the parasitoid. The increasing affordability of next‐generation sequencing technologies will greatly facilitate the analysis of insect‐associated microbial communities and undoubtedly uncover a plethora of as yet unknown protective symbioses. However, a detailed understanding of the host's natural history is indispensable for elucidating the fitness benefits of the symbionts and the molecular basis of symbiont‐conferred protection.